Pengaruh Ekstrakurikuler Pramuka Terhadap Kedisiplinan Siswa Kelas IV SDN 1 Kadilangu Demak - Hasna Nur Alifah; Ramdhani Alifatus Saidah; Zulfa Arifia Rahmadani; Sayyidatul Munnah; Lailatul Fauziah; Inez Avista Rini; Muhammad Imam Zamah Sarin (Badan Penerbit STIEPARI Press, 2023)
This study aims to determine the effect of scout extracurricular implementation on student discipline. Given the number of students who do not show discipline, especially in the school environment, extracurricular scouts can be a solution to overcome these problems. The method used in this study is a type of quantitative research with a descriptive analysis approach method. The research instrument uses a questionnaire or questionnaire through Google Form containing 10 statements with five answer options. The results showed that the implementation of scout extracurricular activities greatly influenced the discipline of grade IV students of SDN Kadilangu 1 Demak. Through the selection of appropriate concepts and strategies in the implementation process, students are able to understand and carry out practical activities exemplified during scouting.